The Role of Islamic Economics and Finance in Activating Sustainable Development (Zien Journal of Social Sciences and Humanities, 2022)
Novelty: Because of the sabotage that afflicted nature, such as air pollution, depletion of natural resources, the problem of carbon, and others, the ideas of the green economy and the ideas of sustainable development, which develop human well-being and preserve the right of future generations to natural resources, have emerged.